SOME ASPECTS OF LEGAL REGULATION OF SUSPENDING A LICENSE ISSUED TO LEGAL ENTITY - B. Y. Dzhamirze (Гуманитарные и юридические исследования)
The article examines the legal nature of suspending a license issued to a legal entity. The author views the suspension of a license issued to a legal entity as administrative-recovery measures.